0.058 mm2 13 Gbit/s inductorless analogue equaliser with low‐frequency equalisation compensating 15 dB channel loss. Issue 2 (1st January 2018) - Balachandran, Arya; Chen, Yong; Choi, Pilsoon; Boon, Chirn Chye
Abstract : An inductorless 13 Gbit/s analogue equaliser with an additional low‐frequency equalisation (LFEQ) to counter the low‐frequency channel losses is presented. An active feedback topology for the proposed equaliser together with negative capacitance circuit is used to extend the bandwidth to compensate a 15 dB channel loss at Nyquist. The LFEQ improves the measured data jitter of the conventional equaliser from 0.41 to 0.12 UI, for a pseudorandom binary sequence of 2 31 − 1. The proposed prototype was implemented in 65 nm CMOS, occupying active area of merely 0.058 mm 2 . It exhibits a power efficiency of 1.07 mW/Gitb/s under a supply voltage of 1.2 V and a BER < 10 −12 .